Children's Food Diversity in Kalianyar Village Bondowoso District as a Stunting-Free Village - Yuana Dwi; Andrielina Firdausih (D'Nursing and Health Journal (DNHJ), 2021)
Introduction: Stunting is a chronic malnutrition problem due to lack of nutritional intake over a long period of time. The direct causes of stunting include maternal factors, poor food quality, food and water safety, inappropriate breastfeeding, etc. This study used a GIAN questionnaire through the East Java Provincial Health Office to collect data. This research aims to examine food diversity and dietary patterns. Method: The research subjects were 15 mothers from the village of Kalianyar who were selected based on posyandu data. Result: The results of this study indicate that more mothers gave birth to colostrum. The results also showed that breastfeeding was dominant at the age of 24 months, namely at the earliest stopped at the age of five months and the longest was at the age of 27 months. The results showed that the predominant children consumed vitamin A rich fruits and several others consumed green vegetables and other types of fruit and vegetables. Conclusion: This is indicated by almost all study subjects who gave colostrum immediately after giving birth and predominantly gave exclusive breastfeeding for six months, although some gave formula milk from the age of five months.